PRELIMINARY STUDY OF DIFFERENT MEDIAS AND VARIOUS PROCESS PARAMETERS ON THE GROWTH OF BLUE-GREEN ALGAE (ANABAENA AMBIGUA) - M.B.VENKATARAMANA REDDY; S.S.LAKSHAMANA RAO; C.S.RAO (International Journal of Pharma and Bio Sciences, 2013)
In this study the fresh water grown Blue-Green Algae (Anabaena ambigua) is studied for its maximum growth. This Blue-Green Algae (Anabaena ambigua) growth is studied in detail in three different media viz., Fog’s media,BG-11, BBM, there was a significant change observed in growth of the species Anabaena ambigua at different light intensities and different media, during 15-days growth. Growth was better in B.G.-11 media at 7000lux light intensity when compared to other media. Biochemical composition (Protein content, carbohydrate content) of the species Anabaena ambigua are estimated. Preliminary studies were done on various parameters like pH,Temperature,light intensity, and agitation on the growth of Blue-Green Algae (Anabaena ambigua).